Microbiological and antibiotic profile of osteomyelitis in tertiary care hospital - A. B., Vijayakumar; Reddy, Yerriswamy Parvatha; B., Suphala; Gopalakrishnan, Ananya; C. S., Vinod Kumar (International Surgery Journal, 2021)
Background: Osteomyelitis has been continuing as the most important cause of morbidity among patients with bone infections. Constant change in the trend of organisms involved and resistance pattern has made management of osteomyelitis cases difficult. With this background present study aimed to look for the changing trends of microorganisms involved in osteomyelitis and their antimicrobial susceptibility pattern. Methods: A total of 100 cases studied over a period of two years. Samples collected were processed by standard microbiological techniques and antimicrobial testing was done as per the clinical and laboratory Standards Institute guidelines. Results: Among 100 cases, 62 were males and 38 were females, with the mean age of all the patient was 51.6±12.32 years. 64% of the patient were diabetic patients. Long bones are most involved with trauma (45%) as risk factor. Staphylococcus aureus (24.2%) predominant pathogen isolated followed by Pseudomonas aeruginosa (21.2%) and Acinetobacter baumannii (16.7%). Antibiotic sensitivity testing of gram positive organisms showed hundred percent sensitivity to vancomycin and gram negative bacteria showed highest sensitivity to cefoperazone+sulbactam, piperacillin+tazobactam, meropenem and imipenem. Conclusions: Osteomyelitis caused by methicillin resistant staphylococcus aureus and carbapenem resistance gram negative bacteria is a serious concern. Since multidrug resistant strains have emerged in osteomyelitis cases, emphasis should be given for hygiene and targeted antibiotherapy.